Establishing Independent and Integrated Student-Run Behavioral Health Clinics to Address Mental Health Disparities in Gainesville, Florida - Gabriel Cartagena; Erin Ferguson; Lori Waxenberg (Journal of Student-Run Clinics, 2021)
Florida continues to rank among the highest states for mental health diagnoses in the nation. Alachua County, which is home to the Gainesville community, continues to experience significant disparity in diagnoses versus access to behavioral health interventions. A significant contributor to this disparity may be the socioeconomic wellbeing of the region, where many individuals report low socioeconomic status and limited access to medical insurance. Gainesville is also home to an advanced network of primary care services and specialties to meet community needs. Among these networks is an established system of student-run medical clinics for uninsured/underinsured patients. New to this system is a psychology graduate student-run behavioral health clinic with an integrated primary care system working hand-in-hand with other medical services. The present article aims to (1) describe the development of an independent, student-run behavioral health clinic model by a graduate student team and (2) describe the implementation/integration of this new clinic model within a free clinic network to meet a need for accessible mental health services, as well as provide patients with an opportunity for integrated care. Current barriers, facilitators, and plans for the models moving forward are discussed.